Odpowiedzi

Najlepsza Odpowiedź!
2010-01-19T18:55:10+01:00
(-4)x(-4)x(-4)=-64
(-4)x(-4)x(-4)x(-4)=256
(-4)x(-4)x(-4)x(-4)x(-4)=-1024

(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)=-1
(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)=1
(-1)x1x(-1)x1x(-1)x(-1)x1x(-1)x1x(-1)x1= 1
2010-01-19T18:57:16+01:00
(-4)x(-4)x(-4)=(-4)³=-64
(-4)x(-4)x(-4)x(-4)=(-4)⁴=256
(-4)x(-4)x(-4)x(-4)x(-4)=(-4)⁵=-1024

(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)=(-1)⁹=-1
(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)=(-1)¹⁰=1
(-1)x1x(-1)x1x(-1)x(-1)x1x(-1)x1x(-1)x1=(-1)⁶x1⁵=1x1=1
2010-01-19T19:02:21+01:00
A) (-4)x(-4)x(-4)=(-4)^3= -64
b)(-4)x(-4)x(-4)x(-4)=(-4)^4=256
c)(-4)x(-4)x(-4)x(-4)x(-4)=(-4)^5=-1024

d)(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)=(-1)^9=-1
e)(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)x(-1)=(-1)^10=1
f) (-1)x1x(-1)x1x(-1)x(-1)x1x(-1)x1x(-1)x1=(-1)^6x1^5=1x1=1